Peningkatan Hasil Belajar Peserta Didik MenggunakanModel Problem Based Learning (PBL) Berbantuan Geogebra pada Materi Jaring-Jaring Kubus dan Balok di Kelas V SDN 002 Tanjung Kampar Riau - Nurrahma Zulita; Dina Amsari; Refiona Andika; Ranti Meizatri (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is motivated by the low mathematics learning outcomes of students on the material of cube and cuboid nets in class V of UPT SDN 002 Tanjung Koto Kampar Hulu due to learning that still does not involve students actively and has not utilized learning models and media that support conceptual understanding. This research aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) model assisted by GeoGebra. The research uses the Classroom Action Research (CAR) method with qualitative and quantitative approaches. Data were collected through observation, tests, and documentation, then analyzed descriptively qualitatively and quantitatively to evaluate the learning process and outcomes. The results of the study indicate that the application of the Problem Based Learning model assisted by GeoGebra is able to improve the quality of learning implementation and student learning outcomes. The quality of learning planning, teacher activities, and student activities has increased to reach the very good category at the end of the action. Student learning outcomes also increased from the poor category at the beginning of the action to the good category at the end of the study, with an average score reaching 83.3. These findings indicate that the GeoGebra-assisted Problem Based Learning model is effective in improving mathematics learning outcomes on the material of cube and cuboid nets in class V of UPT SDN 002 Tanjung Koto Kampar Hulu.